The Effect of Intimate Partner Violence and Probable Traumatic Brain Injury on Mental Health Outcomes for Black Women. Issue 6 (3rd July 2019) - Cimino, Andrea N.; Yi, Grace; Patch, Michelle; Alter, Yasmin; Campbell, Jacquelyn C.; Gundersen, Kristin K.; Tang, Judy T.; Tsuyuki, Kiyomi; Stockman, Jamila K.
ABSTRACT: Severe intimate partner violence (IPV) including loss of consciousness from head injuries and/or strangulation can result in traumatic brain injury (TBI), a brain pathology characterized by altered brain function, cognitive impairment, and mental health disorders, including depression and posttraumatic stress disorder (PTSD). This study examines the prevalence of probable TBI (defined as loss of consciousness from a blow to the head and/or strangulation) and its association with comorbid PTSD and depression among Black women, who experience both higher rates of IPV and greater mental health burden than White and Latina women. Data come from a retrospective cohort study of 95 Black women with abuse history including IPV, forced sex, and childhood maltreatment. About one-third of women (n = 32) had probable TBI. Among them, 38% (n = 12) were hit on the head, 38% (n = 12) were strangled to unconsciousness, and 25% (n = 8) were strangled and hit on the head. Women with IPV history and probable TBI had significantly greater odds of various physical injuries including those that required medical care compared to other abused women. Probable TBI significantly increased comorbid PTSD and depression by 8.93 points ( SE = 3.40 ), after controlling for past violence ( F (4, 90) = 3.67, p < .01 ). Findings from this study reinforce the need to screen women who lost consciousness due to IPV for TBI and facilitate referrals to IPV interventions and mental health treatment.